THE CHARACTERS OF THE MAIN FIGURES IN NICKELODEONâS ANIMATIONS SERIAL OF SPONGEBOB SQUAREPANTS - Irfariati, Irfariati (Widyariset, 2013)
Various uneducating programs including infotainment, entertainment, advertisement, drama, movies overexposing violence and sensuality, and many other destructive ones are always performed on many TV stations. Unconsciously the Nickelodeon animation serial of SpongeBob SquarePants has become great concern and compulsory watching in the morning and afternoon for children. This research is aimed at explaining the characteristics of the main figures in the film and finding the educative values it contains. The research uses Descriptive Analysis Method for observing, recording, elaborating the characteristic of each figure, and exposing the educative values that can be obtained from this cartoon. This research shows that the main figures in the film have positive and negative characteristics. This cartoon also has educative values.